Body posture in the sagittal plane and scoliotic variables in girls aged 7-18 - Wilczyński, Jacek; Habik, Natalia; Paprocki, Michał (Journal of Education, Health and Sport, 2018)
ABSTRACT Introduction. The aim of the study was to analyze the correlation between the variable posture in the sagittal plane and the scoliotic variables. Material and methods. The study involved 28 girls aged 7-18 years with scoliotic posture and scoliosis. Body posture as well as the spine were examined using Moiré’s spatial photogrammetry and the Exhibeon digital radiography method. Based on the size of the spinal curvature, the following were distinguished: scoliotic postures: 1-9° and scoliosis: ≥10°. Results. There were 21 (75%) with scoliotic posture and 7 (25%) with scoliosis. The size of the thoracic kyphosis and lumbar lordosis was normal. Conclusions. Between the body postural variables in the sagittal plane and the scoliotic variables, both positive (direct proportional) and negative (inversely proportional) correlations occurred. In the selection of scoliosis treatment method, the size of the postural variables in the sagittal plane should be taken into account, and each patient’s case should be individually considered.